Extranodal Rosai–Dorfman Disease of the Orbit: Clinical Features of 8 Cases. Issue 6 (November 2016) - Tan, Jeffrey J.; Narang, Sherry; Purewal, Baljeet; Langer, Paul D.; Blaydon, Sean; Schwarcz, Robert M.; McCormick, Steven A.; Kim, Joon Y.; Walrath, Joseph D.; Burt, Benjamin O.; Shinder, Roman
Abstract : Purpose: To report on the presentation, radiography, histology, and treatment of 8 cases of extranodal Rosai–Dorfman disease involving the orbit. Methods: Multicenter retrospective case series. Results: Five males and 3 females had a median age of 10 years (range 2–78 years). Presenting signs and symptoms included proptosis, periorbital pain, palpable mass, blepharoptosis, decreased vision, diplopia, impaired extraocular motility, and afferent pupillary defect. Four patients had bilateral orbital disease, while 4 had unilateral disease. Six cases were extraconal, 1 was intraconal, and 1 was both intra- and extra-conal. Four cases had only extranodal disease without lymphadenopathy (3 of which had localized orbital disease). Diagnosis was confirmed by exam, orbital, and/or systemic radiography, and biopsy in all cases. Treatment strategies included excision or debulking, systemic corticosteroids, chemotherapy, radiotherapy, observation or a combination thereof. At last follow up, 4 patients were disease free, while 4 had residual improved disease. Conclusions: Rosai–Dorfman disease of the orbit is a rare clinical entity. Purely extranodal disease is rare, with isolated orbital disease being exceedingly rare. This study is unique in that 4 of 8 patients had strictly isolated extranodal disease of the orbit. A large majority of the cases had disease in the extraconal space, contrasting with previous reports. In addition, lacrimal gland disease, particularly bilateral involvement, was prominent in the current study. Although there is no consensus on treatment, surgical excision should be attempted if plausible in symptomatic patients especially if the orbit represents a localized site of disease. Abstract : This study reports the presentation, radiography, histopathology, and treatment outcomes of 8 cases of orbital Rosai–Dorfman disease.